2017
DOI: 10.1038/s41467-017-00021-9
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the thermodynamical noise limit in whispering-gallery-mode resonators for ultrastable laser frequency stabilization

Abstract: Ultrastable high-spectral-purity lasers have served as the cornerstone behind optical atomic clocks, quantum measurements, precision optical microwave generation, high-resolution optical spectroscopy, and sensing. Hertz-level lasers stabilized to high-finesse Fabry-Pérot cavities are typically used for these studies, which are large and fragile and remain laboratory instruments. There is a clear demand for rugged miniaturized lasers with stabilities comparable to those of bulk lasers. Over the past decade, ult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(135 citation statements)
references
References 30 publications
3
132
0
Order By: Relevance
“…For instance, when the attentional demands of the task increased, only the spatial stability of deep cells increased, and the stability and precision of deep cells were more strongly modulated by the distance of their place field from the reward zone [8 •• ]. Consistent with these findings, a second study using a similar paradigm reported that superficial cells fired in unique spatial locations across contexts, while deep cells encoded individual landmarks across different contexts [57 • ]. The ability of deep cells to dynamically encode the environment based on landmark or state-dependent variables may serve an adaptive purpose as the activity of deep, but not superficial, cells has been shown to significantly predict task performance [8 •• ].…”
Section: Introductionmentioning
confidence: 88%
“…For instance, when the attentional demands of the task increased, only the spatial stability of deep cells increased, and the stability and precision of deep cells were more strongly modulated by the distance of their place field from the reward zone [8 •• ]. Consistent with these findings, a second study using a similar paradigm reported that superficial cells fired in unique spatial locations across contexts, while deep cells encoded individual landmarks across different contexts [57 • ]. The ability of deep cells to dynamically encode the environment based on landmark or state-dependent variables may serve an adaptive purpose as the activity of deep, but not superficial, cells has been shown to significantly predict task performance [8 •• ].…”
Section: Introductionmentioning
confidence: 88%
“…Along the way of searching for miniature opticalfrequency references based on whispering-gallery modes, work has focused on fluoride crystals [15][16][17][18][19] that offer exceptionally high optical quality factors of Q ∼ 10 12 . Previous research reveals that the fractional frequency stability (FFS) of a laser stabilized to crystals can reach 6 × 10 −14 [16], which requires complex ambient isolation, such as a vacuum chamber, multi-layer temperature control, and vibration isolation.…”
mentioning
confidence: 99%
“…near-infrared and MIR with linewidths at the few kHz level (and less) reachable using different stabilization techniques as those based on ultra-stable cavities [32,44] or whispering gallery mode microresonators [45,46]. In addition, optical frequency comb (OFC) disciplined laser sources [31,47] or directly OFC's as spectroscopic sources [48][49][50][51] provide sub Hz control level of the absolute frequency.…”
Section: Discussionmentioning
confidence: 99%